Comprehensive Supervision for Operational Soundness of Sharia Financial Service Cooperatives - Yadi Nurhayadi (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2015)
Bayt al-Māl wa al-Tamwīl (BMT), which by law in Indonesia BMT is called as Koperasi Jasa Keuangan Syariah (KJKS, Sharia Financial Service Cooperatives), is an ideal sharia banking activities, where those activities involve all of community component: micro, small, medium, and high economic class. BMT is also classified as a constitutional sharia financial institution in Indonesia. Based on that fact, with appropriate to the law, BMT could involve in sharia financial industry and market complexities. The activities and involvements would bring consequences that BMT is included as financial institution that must be supervised and must allow periodic supervision related to its operational soundness. The research in this paper offers an analyzing of BMT operational soundness based on CAMELS rating system plus examination. The system is composed of integration of sharia banking CAMELS rating system that was researched by Muljawan and Sharia Banking Directorate – Bank Indonesia, and BMT performance calculation system that was formulated by Pusat Inkubasi Bisnis dan Usaha Kecil (Pinbuk, Center for Micro Enterprise Incubation). CAMELS plus system is sharia banking CAMELS that accommodates all of aspects of BMT character. CAMELS rating system plus is tested for analyzing BMT operational soundness. The accurate process is applied to synthetic and actual data of BMT, particularly with mathematics, accounting, and banking economics approximation. This system is accurate and capable for processing and analyzing step by step operational soundness of BMT: quantitative and qualitative aspects, including sharia aspects compliance. CAMELS plus assessment results are a composite rating of BMT operational soundness that is classified: quite sound (P1), sound (P2), sound enough (P3), less sound (P4), or unsound (P5); analysis and rating of soundness of every indicator, major area, and component of CAMELS; constructive advices of BMT soundness quality improvements; action plan and analysis of operational continuities. CAMELS plus results, which is continued with action plan and analysis of operational continuities, will give the best solution, whether BMT must stand in or improve its soundness qualities, for quite sound of BMT continuities.